Literatur Review: Tumbuhan Penghasil Asap Cair - Tari Putri Utami Rizki; Nilsya Febrika Zebua (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Liquid smoke is the dispersion of smoke vapor in water. One of the systems for the formation of liquid smoke by condensing the smoke from incomplete combustion of wood. During combustion, compounds from wood include cellulose, helmicellulose and lignin to obtain pyrolysis to produce several compounds such as phenols, carbonyls, acids, furans, alcohols, lactones, polycyclic hydrocarbons, these compounds function as antioxidants, antibacterials and form color and taste. typical. Pyrolysis is a method of breaking down lignocellulosic by limited heat and oxygen and forming gas, liquid or charcoal, the amount of which depends on the types of materials, methods and conditions of pyrolysis. The liquid smoke formation method is carried out through a number of stages starting from pyrolysis, condensation and redistillation. Plants that have been used to produce liquid smoke include coconut shells, nutmeg shells, areca nut shells, bamboo, durian bark, corn cobs, mangrove bark, oil palm and rice husks. The purpose of writing this journal is to find out which plants produce the most liquid smoke.